(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
High level of trauma and locomotion death as a result of damage to the system and Most of the disability is due to acute trauma-tological injuries, regardless of the specialty of young doctor to provide proper and high-quality emergency medical care emphasizes the need to improve their skills. Traumatology, in this article trauma and injuries their prevention measures to receive are provided.